Comparative study of the effectiveness of ozone therapy and laser photobiomulation upon experimental wound repair: systematic review (Research, Society and Development, 2022)
Laser photobiomodulation and ozone therapy are therapeutic possibilities for antimicrobial control and biomodulation of tissue repair. This study aimed to compare the effect of laser photobiomodulation with that of ozone gas in wound healing of experimental lesions on animal's tissues. It was a systematic literature review, which aimed to search for articles of the animal model experimental study according the PRISMA guidelines. The search was made through the electronic articles indexed in the databases: PubMed, BVSalud, Cochrane, Scielo and Google Scholar, based on the DeCS/MeSH descriptors in English and Portuguese. The sample included studies from 2013 to 2020 and methodological quality was assessed using the ARRIVE guideline. A total of 329 of records indentified through database searching. Five studies were selected for the present systematic review according to the inclusion and exclusion criteria outlined for the research. All studies performed histological analysis of the treated tissue sections. Ozone therapy and laser showed a significant difference in favor of repair in different tissues when compared to the findings of the control groups in all studies. When compared to each other, ozone showed superiority over laser in two of the five studies, in addition to two studies having similar results between these two therapies. Regarding the ARRIVE guideline, in the most studies, the meeting criteria was high, with good methodological quality. Most studies highlighted the lack of uniformity in the therapy protocol as the greatest difficulty encountered, although they were unanimous in stating that laser photobiomodulation and ozone therapy contributed to the improvement of the healing pattern.